Emergent Flow of Consciousness (TFE) Theory Sum - Cognito- Ergo - Parra, Alfredo López (Journal of Ecohumanism, 2025)
The Emergent Flow Theory proposes that consciousness arises from the interaction between energy and matter at all levels of existence, giving order and meaning to this relationship. This process allows complex systems, such as the brain, to integrate electrical information into neural networks and transform it into subjective psychic information, experienced as an "I." By combining advances in neuroscience, philosophy, and physical theory, the model redefines consciousness from a reverse emergentist and panpsychic approach. He posits that conscious experience is not a fixed product of the brain, but a continuous flow of external and internal stimuli, subjectively integrated and transformed through thought and emotional processing, with the participation of free will. The theory breaks with the Cartesian dualism of "I think, therefore I am" and adopts an inverse paradigm: "I am, therefore I think", based on biological and existential processes prior to self-reference. In addition, it symbolically reinterprets Einstein’s equation (E=mc²) to explain the interaction between energy (potential information), mass (neural structure) and consciousness (emergent process), where it acts as a regulatory interface between entropy and order, transforming information into subjective experience. Unlike connectionist, emergentist, and dualist theories, this model considers consciousness as a fundamental organizing phenomenon that regulates entropy and enables the emergence of subjective experience in complex systems. The implications span fields such as cognitive neuroscience, clinical psychology, philosophy of being, and theoretical physics, offering an integrative and multidimensional framework for understanding the human experience.